العلاقة بين التخطيط الاستراتيجي وتنمية الموارد البشرية ودور التمويل كوسيط في هذه العلاقة في الجامعات الحكومية الاردنية - كامل عقاب أحمد الخرابشة
This study aimed to highlight the relationship between strategic planning and human resources development, and the impact of the funding process on this relationship in the Jordanian public universities. The study population consisted of all employees in the Jordanian public universities (19,511 employees) while the study sample consisted of rectors, their deputies, assistants and advisers, deans, their deputies and assistants, heads of departments, and directors of financial and human resources in these universities. (521) A simple random sample was chosen and the researcher has developed a questionnaire of which 520 questionnaires have been distributed and 41 7 valid questionnaires returned. The data was collected using SPSS, as well as SEM (AMOS). Averages, standard deviations, as well as the exploratory and assertive factor analysis were used to determine the underlying factors for each field of the questionnaire. The researcher has used the regression analysis to measure the hypotheses of the study. The study has found that there is a significant positive correlation between strategic planning and human resources development, and another significant positive correlation between strategic planning process and funding. The study has also concluded that funding process (the mediating factor) plays an essential role in linking strategic planning with human resources development in such universities. In light of these results, a number of recommendations have been determined including: paying more attention to strategic planning in the Jordanian universities, increasing the interest of the universities in human and intellectual diversity management in human resources management as a strategic approach to the establishment of common and shared values and creating an organizational distinct culture that will enhance creativity among university employees, with a focus on training and increasing and diversifying financial resources of these universities.